(untitled) (AUN INTERNATIONAL CONFERENCE, 2025)
Nigeria faces interconnected security and food crises that pose significant threats to public health and population wellbeing. This paper examines the health implications of these crises through a multidisciplinary lens, analyzing how insecurity directly compromises food systems and nutritional status, leading to cascading health emergencies. We explore the synergistic relationship between conflict, food insecurity, and health outcomes, while proposing integrated interventions that address root causes rather than symptoms. Our analysis reveals that malnutrition rates have increased by 35% in conflict-affected regions, with corresponding rises in maternal mortality, infectious disease prevalence, and childhood stunting. We argue that sustainable solutions require coordinated action across security, agricultural, nutritional, and healthcare sectors, supported by robust surveillance systems and community-based interventions.